Cardiology's best friend: Using naturally occurring disease in dogs to understand heart disease in humans - W. Glen Pyle (Journal of Molecular and Cellular Cardiology Plus, 2025)
Heart diseases are a leading cause of death globally. Laboratory and preclinical animal models of disease have been critical in advancing our understanding of the mechanisms of pathology, creating diagnostic tools, and developing therapeutic interventions. However, fundamental biological dissimilarities between humans and rodents limits their usefulness in research, and the induction of disease in an otherwise healthy animal creates unrealistic conditions under which diseases are typically studied. Dogs are at high risk of acquiring and dying from several naturally occurring heart disorders that also affect people. The spontaneous nature of these conditions, along with highly similar cardiovascular systems, offers unique opportunities to investigate cardiovascular disease in a more relevant model for humans. This review focuses on three common cardiac conditions that impact humans and dogs: dilated cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, and mitral valve disease – comparing mechanisms of disease, diagnostics, and treatments, to identify strengths and present limitations of their utility. It is noted that the benefits of this research are bidirectional, with the potential to translate knowledge and clinical tools used in veterinary medicine to human patients, and vice versa.